The representation of persons with disabilities in literature, comic strip and film - Milošević, Jelena S (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2015)
Exposed to discrimination, segregation and ghettoization, due to ignorance, superstition and fear of unknown, persons with disabilities were treated as a burden and later as patients in compliance with the medical model of disability for centuries. In the second half of the 20th century, under the influence of political and social changes and united activists with disabilities, the social model of disability, based on human rights that belong to everybody, as well as the language of disability have begun to develop. Human awareness has been one of the greatest obstacles on the road of these changes. Therefore, raising awareness is a continuous process requiring persistence, education and motivation of primarily persons with disabilities but the entire public too, with the compulsory usage of all forms of media. In this paper the analysis of films, books and strip whose characters are persons with disabilities indicates how the perception of the media, as a reflection of the society’s attitudes towards disability, has changed in time, from viewing persons with disabilities through the medical model of disability, as passive objects of other person's care, to observing disability from the human rights point of view and social model according to which disability is not a personal characteristic and individual problem, but a social phenomenon.
Keywords: persons with disabilities; human rights; discrimination; models of disability; language of disability; comics; film; literature